Mitochondrial genome sequencing of notorious scuticociliates (Pseudocohnilembus persalinus) isolated from Turbot (Scophthalmus maximus L.). Issue 2 (3rd July 2018) - Gao, Yanqi; Jin, Shibo; Dang, Huifeng; Ye, Shigen; Li, Ruijun
Abstract: Previously, a pathogenic ciliate was isolated from the surface ulcer of a diseased Turbot ( Scophthalmus maximus L.) at an aquaculture farm in North China. After morphological and molecular biological identification based on 18rRNA, the ciliated was identified as the notorious scuticociliates ( Pseudocohnilembus persalinus ). In this study, the whole sequence of the mitochondrial genomic gene of P. persalinus was carried out. The sequencing results showed that the complete sequence of P. persalinus mitogenome was 38, 375 bp. There were 2 rRNAs, 4 tRNAs, and 34 protein-coding genes (PCGs), respectively, located on both the heavy strand and the light stand. 15 PCGs were on the heavy strand, and 19 PCGs on the light strand. Besides, phylogenetic trees among 11 ciliates were constructed based on the sequences of 17 PCGs located in mitogenome using BI methods. The results of clustering showed that P. persalinus and Uronema marinum was the first cluster belonging to the order Scuticociliatida. Our research results will further provide primary data for evolution and classified study of scuticociliates.